Drivers of Sales Performance in Traditional Markeet MSMEs : Digital Literacy, Marketing Capabillity, and Market Orientation - M Fathur Rahman; Kiswanto Kiswanto; Kemal Budi Mulyono; Yahirotun Istamaroh; Mei Anjar Kumalasari (Journal of Economics Education and Entrepreneurship, 2026)
This study aims to analyze the influence of digital literacy, marketing capabilities, and market orientation on sales performance among clothing traders in the traditional market in Johar Market, Semarang City, with entrepreneurial orientation tested as a moderating variable. Digital transformation creates a new dynamic, shifting consumer shopping preferences. The e-commerce phenomenon threathens existence of traditional markets such as Johar Market as a cultural heritage of Semarang City. This approach used quantitative methods. Data collection by survey methods and distributing questionnaires to 242 respondents based on Krejcie & Morgan's formula. The data analysis method used a structural equation model (SEM), with a partial least squares (PLS) approach through SmartPLS 3.1 software to analyze relationships between latent variables simultaneously. The analysis was conducted on the evaluation of outer and inner models. The findings these study indicate entrepreneurial orientation has a positive effect on sales performance, but does not significantly strengthen the relationship between marketing capabilities and market orientation. Different from previous studies, variables in this study focus on MSMEs in traditional markets that have never been tested in previous research